Matrix remodeling and mechanotransduction in in vitro chondrogenesis: Implications towards functional stem cell‐based cartilage tissue engineering - Nirmal S. Remya; Prabha D. Nair (Engineering Reports, 2020)
Abstract Stem cell‐based cartilage regeneration strategies take benefits from functional tissue engineering concepts that effectively exploit cells native mechanotransduction phenomenon for the development of in vitro cartilage constructs. In the present study, stem cell‐seeded constructs were subjected to a dynamic compression of 10% strain, 1 Hz, 4 hours/1 hour each for 7 days. Integrin and Integrin‐associated protein expression was evaluated using real‐time PCR to elucidate the possible mechanotransduction pathway. Matrix remodeling was analyzed by evaluating chondrocyte‐specific extracellular matrix genes as well as by expression of matrix metalloproteinases. The results suggest that dynamic compression significantly influences chondrogenesis by enhancing the expression of chondrocyte‐specific extracellular matrix genes. The results also propose the involvement of Integrin‐mediated signaling pathways in the mechanotransduction events on biomechanical stimuli‐assisted chondrogenesis of stem cells.